Bio-inspired structural colors and their applications. Issue 99 (1st December 2021) - Chen, Fengxiang; Huang, Ya; Li, Run; Zhang, Shiliang; Wang, Baoshun; Zhang, Wenshuo; Wu, Xueke; Jiang, Qinyuan; Wang, Fei; Zhang, Rufan
Abstract : Structural colors, generated by the interaction of interference, diffraction, and scattering between incident light and periodic nanostructured surfaces with features of the same scale with incident visible light wavelengths, have recently attracted intense interest. Abstract : Structural colors, generated by the interaction of interference, diffraction, and scattering between incident light and periodic nanostructured surfaces with features of the same scale with incident visible light wavelengths, have recently attracted intense interest in a wide range of research fields, due to their advantages such as various brilliant colors, long-term stability and environmental friendliness, low energy consumption, and mysterious biological functions. Tremendous effort has been made to design structural colors and considerable progress has been achieved in the past few decades. However, there are still significant challenges and obstacles, such as durability, portability, compatibility, recyclability, mass production of structural-color materials, etc., that need to be solved by rational structural design and novel manufacturing strategies. In this review, we summarize the recent progress of bio-inspired structural colors and their applications. First, we introduce several typical natural structural colors displayed by living organisms from fundamental optical phenomena, including interference, diffraction grating, scattering, photonic crystals effects, the combination of different phenomena, etc. Subsequently, we review recent progress in bio-inspired artificial structural colors generated from advanced micro/nanoscale manufacturing strategies to relevant biomimetic approaches, including self-assembly, template methods, phase conversion, magnetron sputtering, atomic layer deposition, etc. Besides, we also present the current and potential applications of structural colors in various fields, such as displays, anti-counterfeiting, wearable electronics, stealth, printing, etc. Finally, we discuss the challenges and future development directions of structural colors, aiming to push forward the research and applications of structural-color materials.